Photoactivable oxobenzopyranoxazole esters of 5-aminolevulinic acid - Soares, Ana Maria Silva (2016)
Comunicação em painel P51 no 1st European Young Chemists Meeting/ 5th Portuguese Young Chemists Meeting, Guimarães, Portugal, 26-29 Abril 2016.